Philosophical and Theological Foundations as the Foundation for the Development of Islamic Religious Education - Mirnawati Mirnawati; Kasmila Kasmila; Muh. Sukirman; Nur Alifa Ranti; Nurindah Nurindah (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2025)
Islamic Religious Education (PAI) has a strategic role in shaping the personality of students as a whole through the development of intellectual, spiritual, moral, and social dimensions. In the midst of complex globalization and modernization challenges, PAI is required to function not only as a means of religious knowledge transfer, but also as a contextual, reflective, and character-building educational process. This research aims to analyze the philosophical and theological foundations as the foundation for the development of Islamic Religious Education and its implications for educational praxis. The research uses a qualitative approach with the library research method through the analysis of various scientific literature, books, and works of Islamic education thinkers. The results of the study show that the philosophical foundation plays a role in strengthening the rationality, relevance, and contextuality of PAI, while the theological foundation which includes monotheism, worship, morals, and the caliph provides normative and spiritual direction for education. The integration of the two foundations results in a holistic PAI model that is holistic, balanced, and adaptive to the dynamics of modern life. This research emphasizes that strengthening and integrating philosophical and theological foundations is the key to the development of sustainable and meaningful Islamic Religious Education.